Programa sua nota vale dinheiro na arrecadação do Estado do Ceará - Barros, Lucia Maria de Sousa (2010)
The present work is about the Fiscal Education Program created by the Treasury Office of Ceará State(SEFAZ/CE), and it presents the following objectives: to motivate the population in demanding fiscal documents when acquiring goods; to ban fiscal misappropriation, as well as improve tax collection in operations concerning the circulation of goods and services involving inter-state and inter-municipal transport and communication; all of these aims consider the return of benefits to the society. This tax corresponds to 94 % of the state’s own revenue. This campaign can have the participation of the following segments: final consumers; social institutions with no lucrative goals; sport entities; professional inspection councils; community and class associations; philanthropic institutions; religious institutions; cultural institutions; ONG’s. Juridical people (enterprises) are not allowed to participate in this program, as well as people that are directly involved in its operation. This research is one of the first to evaluate the impact of Ceará Government’s program called “your receipt is worth money” . The analysis on the effect of the program “your receipt is worth money”, held by the Treasury Office in Ceará, was performed by the model of linear regression. The used variables were: the collection of ICMS (Brazilian tax upon sales and services); paid values by SEFAZ/CE to the participants in the program; Ceará exportations and monthly interest rates put in practice during the year 2009. The main conclusion about the campaign “your receipt is worth money” is that the customer is motivated to demand receipts during their purchases, which has increased the collection of taxes both in retail and wholesale sectors of business. The sum of collection in these two segments represents 34.16% of ICMS for the state. In general, it was verified that the amounts paid to the participants in the program “your receipt is worth money”, and the interest rates, overnight/selic, have really influenced the collection of ICMS in the wholesale and retail sectors of business in a positive and negative way, respectively.